Matching Cases and Controls Using SAS® Software - Mortensen, Laura Quitzau; Andresen, Kristoffer; Burcharth, Jakob; Pommergaard, Hans-Christian; Rosenberg, Jacob (Frontiers in Big Data, 2019)
Matching is frequently used in observational studies, especially in medical research. However, only a small number of articles with matching programs for the SAS software (SAS Institute Inc., Cary, NC, USA) are available, even less are usable for inexperienced users of SAS software. This article presents a matching program for the SAS software and links to an online repository for examples and test data. The program enables matching on several variables and includes in-depth explanation of the expressions used and how to customize the program. The selection of controls is randomized and automated, minimizing the risk of selection bias. Also, the program provides means for the researcher to test for incomplete matching.